1992
DOI: 10.2355/isijinternational.32.111
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Nitrogen and Carbon Removal from Liquid Iron in Low Content Region under Reduced Pressures.

Abstract: The kinetics of nitrogen and carbon removal from a liquid iron surface in low content regions by blowing Ar gas mixture under reduced pressures have been studied using the samevacuum induction furnace at 1 6000c, respectively. The results obtained are as follows:(1)The nitrogen removal reaction is described as a second order reaction with respect to nitrogen content. The overall reaction rate constant, k~v' decreases with the increase of total pressure. and oxygen and sulfur content.Assumingthat the nitrogen r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 0 publications
5
38
0
Order By: Relevance
“…17) Effect of S on the activity coefficients and density were ignored because content of S considered in the present study is low. K S ( = 40 at 1 873 K) was taken from Sekino et al, 24) which is close agreement with a report by Harashima et al 25) and Nagasaka and Fruehan.…”
Section: )supporting
confidence: 79%
“…17) Effect of S on the activity coefficients and density were ignored because content of S considered in the present study is low. K S ( = 40 at 1 873 K) was taken from Sekino et al, 24) which is close agreement with a report by Harashima et al 25) and Nagasaka and Fruehan.…”
Section: )supporting
confidence: 79%
“…Harashimaet al 4,7) reported that the decarburization rate decreases with the increase of sulphur content in the carbon content range of 10 to 200 ppm. Figure (d=0,15m, T=1 873 K.…”
Section: Effect Of [S]mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Therefore, in order to know the maximum rate of nitrogen removal in steelmaking processes, it is important to understand the reaction mechanism of the interfacial chemical reaction of nitrogen gas with molten iron and the effect of surface active elements on the reaction.…”
Section: Introductionmentioning
confidence: 99%